Rancang Bangun Sistem Informasi Penjualan Berbasis Web Pada Usaha Roti Dapoer Yuri - Evan Rosiska; Rahmat Fauzi (LPPM Universitas Putera Batam, 2020)
Online sales are one of the most important parts of the internet today. The rapid development of technology and the internet in Indonesia has the impact of changes in business change, one of which is the way to buy and sell done online. In the business of Roti Dapoer Yuri still implements the system conventionally, the sales strategy is done directly by delivering products to pt canteens, stalls and shops. When viewed from the development of information system technology that is developing today Dapoer Yuri Bread Business desperately needs a technology to increase sales can be accessed online and accessible anywhere and anytime. The research method used is waterfall model that is through several stages such as needs analysis, system design to be used, program code generation and system testing created. In completing the data so that the goal can be achieved, the data collection technique uses observation and study techniques. With the online sales system has changed the sales system made, where shoppers can make purchases by selecting several types of bread then making the ordering process and continued with the payment process made by transfer through the specified account. Meanwhile, the results of the design of this information system were able to impact the increase in product sales on Dapoer Yuri's bread business effectively.